THE ROLE OF SOCIO-CULTURAL TECHNOLOGIES IN ENHANCING SPIRITUAL PROPAGANDA (Scientific journal of the Fergana State University, 2026)
This article analyzes the concept of technology, the significance of socio-cultural technologies in enhancing spiritual propaganda, and their role in modernizing public administration and developing society. The study examines the integration of modern technologies into governance processes, their effectiveness in implementing social reforms, and their impact on improving public welfare.